Effect of Pradasar Level Training of Satria Nusantara Respiratory Arts on Decreased Symptoms of Depression - Mardatillah Mardatillah (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the extent of the influence of the art of breathing Satria Nusantara at the pre-basic level in reducing symptoms of depression. The method used in this research is an experiment with a Nonequivalent Control Group Design approach, namely by dividing into 2 groups as the experimental group and the control group. Both groups received pre and post tests. The results showed that the results of the data analysis that had been carried out, especially the comparison between the experimental group and the control group on the pre-test post-test difference, that the pre-basic level training in the art of breathing Satria Nusantara had a significant effect on decreasing depression symptoms.